Metabolic fingerprinting of Melastoma malabathricum L. extracts using high-performance liquid chromatography-diode array detector combined with chemometric data analysis - Dian Mayasari, Yosi Bayu Murti, Sylvia Utami Tunjung Pratiwi, Sudarsono Sudarsono (Journal of Applied Pharmaceutical Science, 2021)
Melastoma malabathricum L. is an essential herb that has been traditionally used to treat several ailments such as diarrhea, dysentery, wound, and stomachache. This plant is common across tropical Indo-Pacific archipelagos distributed in various geographical locations of Indonesia. In this study, an effective, accurate, and efficient highperformance liquid chromatography (HPLC) coupled to diode array detectors was developed to evaluate the effect of geographical variations on secondary metabolites of M. malabathricum samples through establishing a fingerprint profile, identification of variations of chromatogram peaks, and determination of anti-methicillin-resistant Staphylococcus aureus (MRSA) activity. Fingerprinting analysis of the extracts was analyzed using chemometric tools including unsupervised data analysis: principal component analysis (PCA) and hierarchical cluster analysis (HCA). PCA values were identified as principal component 1 (PC1) and principal component 2 with 41.229% and 19.208%, respectively. Anti-MRSA activity of all samples showed significant inhibition against MRSA bacteria. The results indicate the significance of considering geographic distribution during field-collection efforts since they demonstrate regional metabolic variations in secondary metabolites of M. malabathricum L., as illustrated by HPLC and their anti-MRSA activity. The results also confirm the utility of this approach as a comprehensive evaluation of metabolic variations based on their different geographical locations and pharmacological effects.
Keywords: Anti-MRSA, chemometrics, HCA, HPLC, Melastoma malabathricum L., PCA.